(untitled) (Precision Medicine Communications, 2022)
Chronic myelogenous leukemia (also called CML or chronic granulocytic leukemia) is a disorder in which the bone marrow generates many white blood cells. There is no recognized etiology for CML in most individuals. Only a few known risk factors for CML development have been identified related to exposure to specific chemicals. It is distinguished by a cytogenetical irregularity comprising a reciprocal translocation between the long arms of chromosomes 22 and 9 [t (9;22)]. CML treatment entails taking a variety of drugs and undertaking additional therapies, all of which can cause unpleasant side effects. In this manuscript, we have sifted through the literature and compiled studies investigating various gene variants affecting the efficacy and adverse effects of the standard of care treatment in CML. Our study shows some promising candidate genes that may be used as a predictor of certain adverse effects of CML treatment. Recommendations are made to employ these genetic variants in clinical medicine.